If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + -7n) = 58 (1 * 2 + -7n * 2) = 58 (2 + -14n) = 58 Solving 2 + -14n = 58 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -14n = 58 + -2 Combine like terms: 2 + -2 = 0 0 + -14n = 58 + -2 -14n = 58 + -2 Combine like terms: 58 + -2 = 56 -14n = 56 Divide each side by '-14'. n = -4 Simplifying n = -4
| p-50=0.75p | | 15+11c=5-18+18c | | -25=3(7n+4) | | x-9=-3x+27 | | y=18x+3 | | -6w-3=-7w-18 | | 4(z+5-24)=5z-13 | | 6x+7x=72 | | (2+yi)*(x-3i)=7-i | | 13b=-12+16b | | 7+6(1w-3)=31 | | -v-10=10-6v | | 5j-10+9j=5+9j | | -14+3x=x | | 6a+7b=19 | | 3x-10=2x+20 | | 5(1a-4)=44 | | 4s=5s+6 | | 3(x-2)=2x+3+x | | X^2-25x+256=0 | | 18=2[x+6] | | 10p=6+7p | | 5x+50=-95 | | g+10=-9g | | a=15-b | | 8n-10=10n+10 | | x=-27+-2.25y | | ab=56 | | 3x-4+2y= | | 2(a-2)=49(2a-4) | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+2) | | -3q-8=10-5q |